Validate artificial intelligence for the diagnosis of periodontal disease - Hameedaldeen, Alhassan; Natto, Zuhair S; Alhassani, Ahmed A; Hayes, Catherine (Tufts University Tisch Library, 2026)
Keywords: Artificial intelligence, Periodontal disease, Radiographic analysis, Diagnostic accuracy, Sensitivity, Specificity, Validation study; Springer Open.